Identification Of Physical Fitness Through Senam Anak Indonesia Hebat Among Junior High School Students In Abepura District. - Rio Wakhid Hujjatul Islam; Zainal Widyanto; Lita Puspita (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
The post-COVID-19 pandemic significantly altered students' pre-pandemic physical activity habits. The presence of poorly managed technology has led to a decline in post-pandemic physical activity. Students now tend to be more active in online gaming technology, resulting in a significant lack of physical activity that impacts physical fitness. An effort to shift the virtual world from the real world is to incorporate the 7 habits of great Indonesian children. Researchers will examine the impact of the implementation of the great Indonesian children's gymnastics program on the physical fitness of Indonesian children. The purpose of this study was to determine the physical fitness level of junior high school students in Abepura District. This study will describe the physical fitness level of Indonesian children, and is part of the descriptive method. Descriptive research aims to describe and test established hypotheses.YPK Diaspora Junior High School Kotaraja has no students with physical fitness below the safe zone. The physical fitness of YPK Diaspora Junior High School students is mostly in the safe zone, with 27 students in the sufficient category and 3 students in the good category. The physical fitness of students at SMP N 4 Jayapura is above the safe zone. This is clearly evident in the physical fitness measurement results, where 19 students were in the Good category and 11 students were in the Very Good category. The physical fitness of students at SMP Al Ikhsan was 12 students in the Poor category and 18 students in the Fair category. The physical fitness of students at SMP YPPK Santo Paulus was above the safe zone, with 15 students in the Good category and 15 students in the Very Good category.The physical fitness of SMP Advent students was 22 students in the safe zone and 8 students were above the safe zone. Differences in physical fitness levels occurred across schools. Based on data obtained, SMP Al Ihsan's physical fitness results were in the red zone. This poor fitness was caused by insufficient physical activity. During the even semester, the researchers observed a lack of physical activity at SMP Al Ihsan. This is because physical activity is restricted for a full month during the even semester due to the Ramadan fasting month of 1445 H.